E-151 Volumetric analysis of endoscopic evacuation of intracerebral hemorrhage. (4th August 2020) - Barros, G; Kellogg, R; Keen, J; Kelly, C; Lele, A; Kim, L; Levitt, M
Abstract : Introduction: Spontaneous intracerebral hemorrhage (ICH) is a neurologically-devastating form of stroke. Minimally-invasive evacuation is increasingly investigated as a primary treatment. Secondary analyses of the MISTIE III (Minimally Invasive Surgery Plus Alteplase for Intracerebral Hemorrhage Evacuation) trial, which used stereotactic catheter drainage, demonstrated promising results among functional outcomes within the surgical arm. A sustained functional outcome advantage was found among patients with less than 15 mL residual clot volume or greater than 70% volume reduction. There is limited research on the effect of post-surgical ICH volumes on functional outcomes for patients specifically undergoing endoscopic evacuations. Objective: Our primary objective is to study how the residual volume and percentage volume reduction of ICH after endoscopic evacuation affects the functional outcome of surgical patients. Methods We conducted a retrospective review of all endoscopic ICH evacuations performed between October 2016 and February 2020 by our institution's cerebrovascular neurosurgery service. Demographics, comorbidities, ICH radiographic characteristics, cardiac status, intra-operative vital signs, medications, post-operative clinical course, and functional outcomes measured as mRS (modified Rankin Scale) were assessed The mRS was assessed at discharge, 30 days, and >90 days. Pre-operative and immediate post-operative CT scans were evaluated. ICH volumes before and after evacuation were manually calculated using the ABC/2 method. Results: A total of 32 endoscopic evacuations among 31 patients were performed. The mean post-operative ICH volume was 15.3 mL (15.2), while the mean percentage volume reduction was 72.8% (24.4). There was a trend of lower post-operative ICH volumes correlating with lower mRS at discharge. Final data and analyses will be presented. Conclusion: Lower post-operative residual clot volumes correlate with improved functional outcome at discharge in patients undergoing minimally-invasive endoscopic evacuation of ICH. Disclosures: G. Barros: None. R. Kellogg: None. J. Keen: None. C. Kelly: None. A. Lele: 1; C; LifeCenter Northwest, Aqueduct Critical Care. L. Kim: 2; C; Microvention, Inc. 4; C; Spi Surgical, Inc. M. Levitt: 1; C; Stryker, Medtronic, Philips Volcano. 2; C; Metis Innovative. 4; C; Synchron, Eloupes, Cerebrotech.